Left the caciques behind: A commentary about contradictions of migration and development in the Philippines - García Martínez, José María (Society Register, 2023)
In this research, I will try to develop a study of the Philippines through a brief review of the bibliography and statistical data analysis. I aim to gather empirical evidence of the causes of extended poverty and unemployment in the country and the high levels of overseas Filipino workers. These social problems and the surge of authoritarianism in the figure of Rodrigo Duterte cannot be adequately explained without referring to the historical legacy of colonialism in the Philippines, the subordinated position of this country in the global division of labour and the structural changes fueled by hegemonic globalization since the last decades of 20th century. Based on scientific research and official data, this article will critically analyze the historical, social, and economic causes that lead to poverty and hardships affecting many Filipino citizens.